Direct Observations of a Shock Traversing Preceding Two Coronal Mass Ejections: Insights from Solar Orbiter, Wind, and STEREO Observations - Yutian Chi; Chenglong Shen; Zhiyong Zhang; Mengjiao Xu; Dongwei Mao; Junyan Liu; Can Wang; Bingkun Yu; Jingyu Luo; Zhihui Zhong; Yuming Wang (The Astrophysical Journal Letters, 2024)
The three successive coronal mass ejections (CMEs) that erupted from 2023 November 27–28, provide the first opportunity to shed light on the entire process of a shock propagating through, sequentially compressing, and modifying two preceding CMEs using in situ data from Solar Orbiter, Wind, and STEREO-A. We describe the interaction of the three CMEs as follows: CME-1 and CME-2 interacted with each other at distances close to the Sun. Subsequently, the shock (S3) driven by CME-3 caught up with and compressed ICME-2 before 0.83 au, forming a typical shock–ICME interaction event observed by the Solar Orbiter. The S3 continued to propagate, crossing ICME-2 and propagating into ICME-1 as observed by Wind, and completely overtaking both ICME-1 and ICME-2 at STEREO-A. The interaction between S3 and the preceding two ICMEs leads to a clear compression of preceding ICMEs including an increase in magnetic field (∼150%) and a reduction in the interval of ICMEs. It presents direct and compelling evidence that a shock can completely traverse two preceding CMEs, accompanied by a significant decrease in shock strength (magnetic compression ratio decrease from 1.74 to 1.49). Even though the three ICMEs interact significantly in the heliosphere, their magnetic field configurations exhibit coherence at different observation points, especially for ICME-3. Those results highlight the significant implications of shock–CME interactions for CME propagation and space weather forecasting.